Too many curses - Martinez, A. Lee (Tor, 2008)
Serving a wizard who has transformed innumerable victims into monsters and other cursed forms and then imprisoned them in his castle, housekeeper Nessy faces a disastrous uprising when the wizard suddenly dies.